Stress Corrosion Behaviour of Advanced Materials Like Al1100/Sic Nano Composites (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
The stress corrosion resistance of AL1100/SiC  Nano Composites metal matrix composites  (MMC’s) in high temperature acidic media has  been evaluated using an autoclave. The liquid  melt metallurgy technique using vortex method  was used to fabricate MMC’s. SiC Nano  Composites particulates of 50-80 μm in size are  added to the matrix. AL1100 containing 2,4,6  weight percentage of SiC Nano Composites are  prepared. Stress corrosion tests was conducted  using weight loss method for different exposure  time, normality and temperature of the acidic  medium. The corrosion rates of composites was lower to that of matrix AL1100 alloy under all  conditions.
Keywords: SiC Nano Composites; MMC’s; Vortex method; Stress corrosion; Autoclave